Novel Contrast‐Enhanced Ultrasound Evaluation in Neonatal Hypoxic Ischemic Injury: Clinical Application and Future Directions. (26th June 2017) - Hwang, Misun; De Jong, Robert M.; Herman, Stephan; Boss, Renee; Riggs, Becky; Tekes‐Brady, Aylin; Spevak, Melissa; Poretti, Andrea; Soares, Bruno P.; Bailey, Christopher R.; Dunn, Emily; Shin, Samuel S.; et al.
Abstract : Sensitive, specific, and safe bedside evaluation of brain perfusion is key to the early diagnosis, treatment, and improved survival of neonates with hypoxic ischemic injury. Contrast‐enhanced ultrasound (US) imaging is a novel imaging technique in which intravenously injected gas‐filled microbubbles generate enhanced US echoes from an acoustic impedance mismatch. This article describes contrast‐enhanced US imaging in 2 neonates with hypoxic ischemic injury and future directions on developing quantitative contrast‐enhanced US techniques for improved characterization of perfusion abnormalities. The importance of studying the temporal evolution of brain perfusion in neonatal hypoxic ischemic injury is also highlighted.